Antecedents to willingness to boycott among Malaysian Muslims - Abdul Latif, Samshul Amry; Abdul Talib, Asmat Nizam (IGI Global, 2015)
This chapter examines the motivations and willingness to boycott of Malaysian Muslim consumers. Based on an ongoing boycott incited by the Palestinian-Israeli conflict in the Middle East, the boycott movement targets American-originated firms operating in Malaysia. To examine the factors, two firms were selected based on their market presence, consumer familiarity, and product affordability. In total, 577 questionnaires were distributed to Muslim university students, and the results were validated through Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. Three factors were found to be significant in predicting the willingness to boycott; they were self-enhancement, perceived egregious behavior, and country image. This chapter addresses boycott motivations from the context of Malaysian Muslims quantitatively, based on an international issue strongly related to Muslims. The results may have some implications on multinational firms, non-government organizations, policymakers, and consumers.